边缘处的捍卫与悲叹 ：张曦娜和英培安的华校生题材之比较 = Defence and lament from the margin : a comparative study of the representation of the Chinese-educated groups in Teoh Hee La’s and Yeng Pway Ngon’s fiction - 纪庆聆 Kee, Colina Keng Ling (2010)
二战后，新加坡华人社会出现了两种不同教育背景的语文群体，即英校生和华校生。英校生在社会中占据较高的位置，华校生则多在政治领域中败下阵来，在谋职方面也处处碰壁。目睹英文群体的逐步壮大，华校出身的作家们感受到自己深爱的母语文化遭受排挤，殖民语言在后殖民新加坡语境里更受重视的一种吊诡的、不平等的语言现象。张曦娜和英培安本身是成长于1950年代的华校生，他们的文化忧思，在各自的小说人物身上得到了不同形态的文学表述。本文以一位女作家和男作家的小说为研究对象，借助女性后殖民理论中“边缘化”的概念，从而比较两人刻划华校生形象时不同的文学再现。论文发现，张曦娜笔下女性在母语文化的坚守上有着“不让步”的积极性。她们以一种理想式的“捍卫”姿态出现，企图重建“华校生”的受挫心灵。英培安则是走向一种较为极端的“悲叹”，通过彰显男性的弱点来勾勒“华校生”处境的卑微，进而形成一种回应主流意识形态的抵抗性书写。尽管表述不同，两位都是把关怀点聚焦在这群遭边缘化的“华校生”身上，引起我们对语文现象不平等的反思。 After World War II, the Chinese community in Singapore witnessed a divide according to their different educational background, namely, the English-educated and the Chinese-educated. The English-educated generally held higher positions in society, while the Chinese-educated were given fewer opportunities in the political arena, and many were marginalized in terms of employment, professional advancement and climbing the social ladder. As the number of English-educated grew, Chinese-educated writers felt the impact of the discrimination against their mother tongue, in addition to the fact that the language of an earlier colonial power had come to assume a greater importance in postcolonial Singapore.